Про періодизацію історії первісного суспільства - Бунятян, К.П. (Археологія, 1989)
Задача социологической интерпретации археологического материала настоятельно требует осмысления логики исторического процесса и выделения в нем качественных этапов, в данном случае в рамках первобытнообщинной формации. Обращение археологов к существующим периодизационным схемам затруднено не столько в силу существующих разногласий между различными исследователями, решающими эту задачу, сколько в связи со спецификой археологического материала. Предлагаемые до сих пор критерии периодизации не находят отражения в археологическом источнике и представляют собой сложные явления для реконструкции. Выход из создавшейся ситуации заключается в построении периодизации на основе развития производительных сил. Именно в их изучении археология накопила значительный опыт, который может быть отправным моментом для изучения связанных с ними социально-экономических отношений. В рамках присваивающей экономики, исходя из уровня развития производительных сил, намечены три основных этапа, с которыми соотносятся возникновение тех или иных институтов, их роль и функции. The problem of sociological interpretation of archaeological data persistently necessitates to comprehend the logic of the historical process and to distinguish qualitative stages in it, in this case within the frames of the primitive communal formation. Usage of the existing periodization schemes by archaeologists is difficult because of the specificity of archaeological data rather than because of the differences existing between a number of researchers engaged in this problem. The now suggested periodization criteria lack confirmation in the archaeological source are a complex phenomena to be reconstructed. The situation may be overcome if constructing periodization on the basis of development of productive forces. When studying productive forces archaeology has stored considerable experience which may be a starting-point to analyze socio-economic relations resulted from them. Within the frames of the appropriating economy and coming from the level of the development of productive forces, three main stages of appearance of certain institutions, their role and functions are outlined.